Forecasting model of crude oil price instability in asean-5 countries - Chin, Jia Hui (2023)
Crude oil plays an essential role in our daily life today as it serves as raw materials in the industrial process, fossil fuels for transportation, fertilizers in farming, power generators, etc. Crude oil price instability can have negative economic, social, and political consequences. It affects industries and consumer purchasing power and can cause uncertainty for businesses and investors. It can also increase income inequality and affect geopolitical relationships between nations. This research study examined the factors affecting crude oil prices by investigating the relationships among the exchange rate, inflation rate, interest rate, GDP per capita, production of crude oil, and crude oil price. This research study focused on ASEAN5 countries, including Brunei, Indonesia, Malaysia, Singapore, and Thailand. This research study utilized a panel model to determine the relationships among the variables with the crude oil price and the ARIMA model to individually forecast the crude oil price in ASEAN-5 countries. This study used secondary data from the World Bank, Index Mundi, the United States Department of Agriculture, and the U.S. Energy Information Administration. The data period adopted was annual data from 2007 to 2021 for the panel model, while monthly data from January 2017 to September 2022 for the ARIMA model. The empirical results show that the Period Fixed Effect Model is the best panel model. There are significant relationships among exchange rate, inflation rate, GDP per capita, production of crude oil, and crude oil price except for interest rate with the crude oil price. The ARIMA model results show the model specifications for all five countries is ARIMA (1,1, 1) model and the crude oil price in ASEAN-5 countries is volatile and unstable during the estimated period. The ex-post forecast revealed an increasing trend for Brunei, Indonesia, and Malaysia and a decreasing trend for Singapore and Thailand. Therefore, policymakers, businesses, and individuals should monitor and respond to changes in crude oil prices to mitigate their impacts.